In vivo Inhibition of the 3-Dehydroquinate Synthase by 7-Deoxysedoheptulose Depends on Promiscuous Uptake by Sugar Transporters in Cyanobacteria - Rapp, Johanna; Wagner, Berenike; Brilisauer, Klaus; Forchhammer, Karl (Frontiers in Microbiology, 2021)
7-Deoxysedoheptulose (7dSh) is a bioactive deoxy-sugar actively excreted by the unicellular cyanobacterium Synechococcus elongatus PCC 7942 (S. elongatus) but also Streptomyces setonensis. In our previous publications we have shown that in S. elongatus, 7dSh is exclusively synthesized by promiscuous enzyme activity from an inhibitory by-product of radical SAM enzymes, without a specific gene cluster being involved. Additionally, we showed that 7dSh inhibits the growth of cyanobacteria, but also the growth of plants and fungi, presumably by inhibiting the 3-dehydroquinate synthase (DHQS), the second enzyme of the shikimate pathway, as the substrate of this enzyme strongly accumulates in cells treated with 7dSh. In this study, by using purified DHQS of Anabaena variabilis ATCC 29413 (A. variabilis) we biochemically confirmed that 7dSh is a competitive inhibitor of this enzyme. By analyzing the effect of 7dSh on a subset of cyanobacteria from all the five subsections, we identified different species whose growth was inhibited by 7dSh. We also found that in some of the susceptible cyanobacteria import of 7dSh is mediated by structurally different and promiscuous transporters: 7dSh can be taken up by the fructose ABC-transporter in A. variabilis and via the glucose permease in Synechocystis sp. PCC 6803 (Synechocystis sp.). In both cases, an effective uptake and thereby intracellular enrichment of 7dSh was essential for the inhibitory activity. Importantly, spontaneous mutations in the sugar transporters of A. variabilis and Synechocystis sp. not only disabled growth of the two strains on fructose and glucose, respectively, but also almost abolished their sensitivity to 7dSh. Although we have clearly shown in these examples that the effective uptake plays an essential role in the inhibitory effect of 7dSh, questions remain about how 7dSh resistance works in other (cyano)bacteria. Also, the involvement of a putative ribokinase in 7dSh resistance in the producer strain S. elongatus remained to be further investigated. Overall, these data establish 7dSh as the first allelochemical targeting the shikimate pathway in other cyanobacteria and plants and suggest a role of 7dSh in niche competition.